HUBUNGAN ANTARA GOAL ORIENTATION DENGAN SENSE of SCHOOL BELONGING PADA MAHASISWA DEPARTEMEN PSIKOLOGI UNIVERSITAS PENDIDIKAN INDONESIA - Pratiwi, Indah (2017)
The present study is aimed to find out the relation between goal orientation and sense of school belonging (SoSB) of college students of psychology department in Indonesia University of Education. The study employs quantitative method and correlation technique. The subject of the study is 199 students of psychology department in Indonesia University of education and chosen through quota sampling. The data are collected by using questionnaire method and Psychological Sense of School Membership (PSSM) instrument to measure SoSB and instrument of goal orientation. The results of the study show that there is no relation between goal orientation pasticularly the type of mastery-approach and mastery-avoidance with sense of school belonging, and there is negative relation between performance-approach, performance-avoidance orientation with sense of school belonging.---- Penelitian ini bertujuan untuk mengetahui hubungan antara goal orientation dengan sense of school belonging (SoSB) pada mahasiswa Departemen Psikologi Universitas Pendidikan Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik korelasional. Subjek penelitian ini berjumlah 199 mahasiswa Departemen Psikologi Universitas Pendidikan Indonesia dan diambil dengan teknik quota sampling. Pengumpulan data dilakukan dengan metode kuesioner menggunakan instrumen Psychological Sense of School Membership (PSSM) untuk mengukur SoSB dan instrumen goal orientation. Hasil penelitian menunjukkan tidak terdapat hubungan antara goal orientation jenis mastery-approach dan mastery-avoidance orientation dengan sense of school belonging, dan terdapat hubungan negatif antara performance-approach dan performance-avoidance orientation dengan sense of school belonging.